2011
DOI: 10.1063/1.3573511
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Kapitza resistance across a bicrystal interface

Abstract: The Kapitza resistance across a Si bicrystal interface was measured using a pump probe optical technique. This approach, termed time resolved thermal wave microscopy (TRTWM), uses ultrafast laser pulses to image lateral thermal transport in bare semiconductors. The sample geometry is that of a Si bicrystal with the vertically oriented boundary intersecting the sample surface. High resolution transmission electron microscopy of the boundary region revealed a thin SiO2 layer at the interface. By comparing experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 23 publications
7
22
0
Order By: Relevance
“…The pump is focused at the center of the fiber and the probe is scanned on the surface to map the thermal wave profile. This configuration is similar to a study on Si bicrystal interface 88 reported previously and implements 400 nm pump and 800 nm probe beams based on Ti:sapphire femtosecond laser. One notable difference from Ref.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…The pump is focused at the center of the fiber and the probe is scanned on the surface to map the thermal wave profile. This configuration is similar to a study on Si bicrystal interface 88 reported previously and implements 400 nm pump and 800 nm probe beams based on Ti:sapphire femtosecond laser. One notable difference from Ref.…”
supporting
confidence: 56%
“…For these studies, it is critical to avoid development of surface topography around the interface during polishing. 88 It should be realized that while TR approaches are effective in providing conductivity measurements with several micron resolution, they are not appropriate for investigations that require measurement of thermal properties averaged over tens of microns such as the effective conductivity of SiC fiber composites or highly porous materials. For these applications, one would rely on laser flash apparatus or infrared pyrometry.…”
Section: Practical Considerations For Implementation Of Tr Techniquesmentioning
confidence: 99%
“…Both structures contain an amorphous SiO 2 layer with a thickness of 4.6 nm which is close to that found in some experiments. 28 For comparison, we also model the Sijh-BNjAl structure, i.e., the crystalline nanoscopic layer, which contains 15 h-BN layers whose ½11 20, ½1 100, and ½0001 directions are aligned, respectively, in the x, y, and z directions. In all three structures, the [001] direction of the Si lead and the [111] direction of the Al lead are aligned in the z direction and the length of Si and Al leads in the z direction is 400 and 300 unit cells, respectively.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The measured total TBC, which includes thermal resistance of amorphous SiO 2 and TBC of Si/SiO 2 interface, agreed well with those obtained from previous experiments and numerical simulations. [68][69][70] Using this process, various interface structures were obtained by varying the sintering temperature (T s ), pressure, surface chemical treatments, and crystal orientations. Figure 6 shows TEM images of the obtained interfacial structures and their TBC measured by the TDTR method.…”
Section: Engineering Phonon Transport At Sintered Interfacesmentioning
confidence: 99%